Altering Intracellular Localization of the RNA Interference Factors by Influenza A Virus Non-structural Protein 1 - Wang, Hua; Tian, Zhonghui; Xu, Yan; Wang, Qi; Ding, Shou-Wei; Li, Yang (Frontiers in Microbiology, 2020)
Influenza A virus (IAV) causes seasonal infections and periodic pandemics in humans. The non-structural protein 1 (NS1) of IAV is the main viral antagonist of the innate immune responses that play a key role in influenza pathogenesis. However, the mechanism to disrupt the host cell homeostasis by IAV NS1 remains poorly understood. Here, we show that expression of NS1 from the WSN strain, but not PR8 strain, of IAV, markedly induced nuclear import of the host RNA interference (RNAi) factors such as Argonaute-2 and microRNA 16. We found that the single residue substitution of aspartic acid with histidine at position 101 (D101H) of IAV-PR8 NS1 was sufficient to induce the nuclear import process and to enhance the virulence of IAV-PR8 in mice. However, we observed no significant differences between the wild-type and mutant IAV-PR8 in virus titers or induction of the interferon response in lung tissues, indicating a novel role of NS1 in the virulence determination of IAV in a mammalian host. Moreover, our bioinformatic analysis of 69,057 NS1 sequences from all IAV subtypes deposited in the NCBI database revealed that the NS1-H101 gene of IAV-WSN was widespread among H1N1 viruses isolated in 1933 but disappeared completely after 1940. Thus, IAV NS1 (H101) is a mutation selected against during evolution of IAV, suggesting that mutation H101 confers an important biological phenotype.